Cloud-based Architecture Integrated with IoT Framework for Smart Agriculture Applications for Increased Productivity (International Journal of Food and Nutritional Sciences, 2022)
In recent decades, advances in computer technology have become more important in all areas, including transportation, healthcare, smart online purchases, smart education, and warehouses. Computing technology makes it simpler for man to adobe data in every industry and business. The goal of these innovations in every area is to give real-time, dependable, efficient, and secure data when it is required. Furthermore, computer technology creates a user-friendly environment for everyone involved in it to readily utilize the technology. The major objective of technology, on the contrary hand, is to improve communication in all areas since information and communication have always been vital components of the human race. This article investigates cloud-based architecture linked with an IoT framework for smart agricultural applications with the goal of increasing crop production.